Application of Virtual and Augmented Reality to the Field of Adult Education - Jihye Oh; Soo Jeoung Han; Doo Hun Lim; Chang Sung Jang; In Tak Kwon (Adult Education Research Conference, 2018)
This research reviews the extant literature and web resources on Virtual Reality (VR) and Augmented Reality (AR) to provide new insights and future direction of adult learning. Based on the review, we discuss implications for research and practice on the use of VR and AR in the field of Adult Education.
Keywords: virtual reality; augmented reality; training and development